Can exposure to neem oil affect the spermatogenesis of predator Ceraeochrysa claveri? - Garcia, Ana Silvia Gimenes [UNESP]; Scudeler, Elton Luiz [UNESP]; Pinheiro, Patricia Fernanda Felipe [UNESP]; dos Santos, Daniela Carvalho [UNESP] (Springer Nature, 2019)
Novel biological control methods and integrated pest management strategies are basic requirements for the development of sustainable agriculture. As a result, there is a growing demand for research on the use of plant extracts and natural enemies such as the green lacewing, Ceraeochrysa claveri, as natural pest control methods. Studies have shown that although natural compounds such as neem oil (Azadirachta indica) are effective as pest control strategies, they also cause sublethal effects on nontarget insects, such as C. claveri. The aim of this study was to examine the effects of neem oil on C. claveri testes. C. claveri larvae were fed Diatraea saccharalis eggs, which were pretreated with 0.5%, 1%, and 2% neem oil. Testes were collected from larvae, pupae, and adults and analyzed using light and electron (transmission and scanning) microscopy. Changes in cellular stress and possible cell death were also determined by TUNEL assay and the marker HSP-70. The results showed that neem oil affects the organization and distribution of cysts in the testes and the normal sequence of cyst development, causing a delay in spermatogenesis in the testes of treated insects. Tests for cellular stress and DNA fragmentation indicated there was no cellular alteration in the treated groups. Although neem oil does not induce cell death or changes in HSP-70 expression, this biopesticide negatively impacts the process of spermatogenesis and could decrease the perpetuation of this species in the agroecosystem, indicating that the use of neem oil in association with green lacewings as a biological control should be carefully evaluated.
Keywords: Biopesticide; Green lacewing; Morphology; Testes; Ultrastructure